Evaluation of the effect of education on perceived stress of mother candidates for amniocentesis - Shahnaz Mojahed; Fariba Reyhanizadeh; Razieh Sadat Tabatabaei; Ali Dehghani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Amniocentesis is one of the methods for diagnosing prenatal abnormalities. Pregnant women with high-risk fetal screening results are the candidates for amniocentesis. Most of these women are afraid of this procedure because they predict that the test will be painful and worried about its adverse effects on pregnancy, fetal injury, or the risk of maternal death. Therefore, the aim of this study was to determine the effect of education on the perceived stress of mothers who are the candidates for amniocentesis. MATERIALS AND METHODS: The present study was a quasi-experimental, two-group clinical trial with a parallel design. This study was in three stages: pretest (before intervention), posttest (after intervention), and after amniocentesis. This study was performed on 80 pregnant women who were the candidates for amniocentesis (15-20 weeks of pregnancy) with high-risk fetal screening results referred to the perinatology clinic in Yazd in 2020. The intervention package included training and using breathing techniques, broadcasting educational animations on how to perform amniocentesis, expressing experiences by people who had experienced amniocentesis, and finally visiting the amniocentesis site and getting to know the relevant perinatologist. Data collection tools were demographic and midwifery profile questionnaires and Cohen perceived stress. SPSS software version 16 was used for statistical analysis of data. RESULTS: The results showed that the research units had high stress at the beginning of the study. The perceived stress score at the beginning of the study in the intervention group was 30.1750 ± 6.53153 and in the control group was 28.2750 ± 8.57841. After the intervention, the participants' stress level decreased below the cutting point. In the experimental group, the mean stresses after the intervention and after amniocentesis were significantly lower than before the intervention; however, after amniocentesis, it was somewhat higher than the postintervention stage. In the preintervention stage, the mean stress score between the two groups was not statistically significant. The difference after the intervention between the two groups was significant (P < 001.0); however, in the postamniocentesis stage, the difference in stress was not significant. After the intervention and after amniocentesis, the perceived stress of pregnant mothers in the experimental group was less than the control group. CONCLUSION: Considering that the perceived stress in amniocentesis candidate mothers was high in the present study, so that after performing the method, mothers left the center with high stress, it is very important to pay attention to its psychological aspects. Therefore, it is suggested that educational interventions before and during amniocentesis be considered for them along with psychological support and follow-up care after amniocentesis.